Cartografia tátil para alunos com deficiência visual: a experiência do globo adaptado - Jordão, Barbara Gomes Flaire [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The mandatory of inclusion in regular education highlighted the challenges of teacher in the classroom. From the release in the Brazilian Ministry of Education (MEC) website on the evolution of enrollment in special education; there was, between 1998 and 2006, an increase of 640% enrollment in ordinary schools, due to the inclusive system in place, plus the growth of 28% enrollment in schools and special classes. Through these data and visits to common classes and special institutions, it was possible to justify the execution of the research in the area of inclusive education which questioned the role of Geography in this scenario. As a field of research or as a school discipline, Geography is often linked to the perception in the visual field; therefore, people with visual impairment have major obstacles when studying science. In this work I opted for the production of an adapted world globe for visually handicapped students, which could encompass abstract subjects of Geography, such as the coordinates. It is intended that this research serves as an incentive to minimize the gap between today's school and the school that one wants to have in Brazil through the production of a material accessible to teachers, parents and people interested in teaching without restriction.

A obrigatoriedade da Inclusão no ensino regular evidenciou os desafios do professor em sala de aula. A partir da divulgação no portal do Ministério da Educação (MEC) sobre a evolução das matrículas na educação especial, verificou-se, no período de 1998 e 2006, um crescimento de 640% das matrículas em escolas comuns, devido ao sistema inclusivo instaurado, somados ao crescimento de 28% de matriculas em escolas e classes especiais. Com esses dados e as visitas realizadas a salas comuns e instituições especiais, foi possível fundamentar a realização de uma pesquisa na área de ensino inclusivo onde questionou-se o papel da Geografia neste cenário. Seja como área de pesquisa quanto como disciplina escolar, a Geografia está comumente ligada à percepção no campo da visão, portanto, as pessoas com deficiência visual encontram maiores obstáculos quando lidam com esta ciência. Neste trabalho optou-se pela produção de um globo terrestre adaptado para este público, que pudesse dar conta, sobretudo de temas abstratos da Geografia, como no caso as Coordenadas Geográficas. Pretende-se que esta pesquisa sirva de incentivo para amenizar o abismo existente entre a escola que se tem e a escola que se quer ter no Brasil, através da produção de um material acessível aos professores, pais e interessados num ensino sem restrição.
Keywords: Cartografia; Educação inclusiva